CROSS-SPECTRAL ANALYSIS OF METOCEAN DATA FOR MALAYSIAN WATERS - OTHMAN, NURUL ASHIKIN (2014)
Random wind speed (WS) and significant wave height (SWH) are of the crucial parameters that need to be assessed to attain a full understanding of metocean loadings. Relationship between these parameters is examined by statistical analysis for better predictions of environmental loads forecast. In this research presented herein, the relationship of WS and SWH parameters are assessed with the development of cross-spectral analysis. This bivariate extension of spectral analysis is the significance of this study as it enhances the findings of spectral densities for both SWH and WS. Frequencyranges of dominant peaks are the researcher's interest with concern of the influences from North East Monsoon (NEM) and South West Monsoon (SWM) of South China Sea (SCS) region. Similar pattern of spectral and cross-spectral are observed with related significance ranges of spectral peaks. Coherence and phase spectrum acquired in these research findings have indicated existence of correlation between SWH and WS at significance frequency ranges for the measured metocean data in the Malaysian waters.